An evaluation of ASEAN tourism websites / Noel Scott and Rodolfo Baggio - Baggio, Rodolfo (Faculty of Hotel & Tourism Management Universiti Teknologi MARA, Selangor, 2009)
The Internet has proved to be a widespread medium and an integral part of the habits of millions of users. An effective online communication strategy is considered nowadays a key element to achieve a competitive advantage on the market, to satisfy actual and potential tourists' information needs in a highly competitive way and to acquire new clients. All the ASEAN countries have implemented some kind of official tourism portal to promote their own destinations. An analysis of these tourism websites has been performed by collecting end-user evaluations and mapping contents and services offered online. The results of this survey are presented and compared with the general behaviour of the European Internet users regarding the use of the network as a tool to gather information, and to acquire travel services